Recognition of GT mismatches by Vsr mismatch endonuclease - Fox, Keith R. (Oxford University Press, 2000)
The Vsr mismatch endonuclease recognises the sequence CTWGG (W = A or T) in which the underlined thymine is paired with guanine and nicks the DNA backbone on the 5′-side of the mispaired thymine. By using base analogues of G and T we have explored the functional groups on the mismatch pair which are recognised by the enzyme. Removal of the thymine 5-methyl group causes a 60% reduction in activity, while removing the 2-amino group of guanine reduces cleavage by 90%. Placing 2-aminopurine or nebularine opposite T generates mismatches which are cut at a much lower rate (0.1%). When either base is removed, generating a pseudoabasic site (1′,2′-dideoxyribose), the enzyme still produces site-specific cleavage, but at only 1% of the original rate. Although TT and CT mismatches at this position are cleaved at a low rate (~1%), mismatches with other bases (such as GA and AC) and Watson–Crick base pairs are not cleaved by the enzyme. There is also no cleavage when the mismatched T is replaced with difluorotoluene.